Correlation between Periodontal Health Status and Salivary Matrix Metalloproteinase-9 Levels in Smoker and Non-Smoker Chronic Periodontitis Patients (A Comparative Study) - Sura D. Jassim; Lekaa M. Ibrahim (College of Dentistry/ University of Baghdad, 2016)
Background: Periodontal diseases are inflammatory diseases affecting the supporting tissues of the teeth. One of the leading environmental factors that are closely related not only to the risk but also to the prognosis of periodontitis is smoking. This study aimed to evaluate the influence of smoking on periodontal health status and to measure the levels of matrix metalloproteinase-9 in smokers and nonsmokers chronic periodontitis patients, also it aimed to test the correlation between the levels of matrix metalloproteinase-9 and the clinical periodontal parameters. Materials and Methods: Five milliliters samples of un-stimulated whole saliva and full-mouth clinical periodontal recordings (plaque index, gingival index, bleeding on probing, probing pocket depth and clinical attachment level) were obtained from forty patients of two groups (non smokers with chronic periodontitis and smokers with chronic periodontitis). All subjects were systemically healthy males, with age range (35-50) years. Salivary matrix metalloproteinase-9 levels were analyzed by using Enzyme-linked Immunosorbent Assays. Results: Statistical analysis revealed that probing pocket depth and clinical attachment level were higher in smokers than non smokers, while there were decreases in the numbers of bleeding sites in smoker when compared with non smoker subjects. Salivary matrix metalloproteinase-9 levels were significantly higher in smoker with chronic periodontitis patients than their non smoker counterparts. Conclusion: Salivary matrix metalloproteinase-9, as a biomarker, could reflect the increased periodontal tissue destruction due to the smoking.